Digital Marketing Strategies to Increase Brand Awareness in the E-Sports Industry - Rifky Verdiansyah; Guruh Taufan Hariyadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the influence of digital marketing strategies, including Content Marketing, Influencer Marketing, and Community Marketing, on Brand Awareness within the e-sports industry. Alongside the rapid growth of the e-sports sector both globally and in Indonesia, effective digital marketing has become essential for brands to enhance visibility and audience engagement. Employing a quantitative research design, data were collected through an online questionnaire distributed to 200 respondents and analyzed using SmartPLS version 4.1.1.2. The analysis results show that the research model achieved an Adjusted R-Square value of 0.752, indicating that the independent variables were able to explain 75.2% of the variance in Brand Awareness. The findings further reveal that Content Marketing, Influencer Marketing, and Community Marketing all have a significant positive effect on Brand Awareness, underscoring their critical role in shaping consumer perception and engagement. These results highlight the importance of integrated digital marketing strategies in building strong brand recognition, fostering community interaction, and enhancing consumer loyalty in the highly competitive e-sports landscape. By leveraging these strategies, companies can not only strengthen their market position but also create deeper relationships with e-sports fans. This study contributes to the growing body of literature on digital marketing within the creative economy and offers practical insights for marketers seeking to develop targeted and effective promotional strategies in the dynamic e-sports environment.